Pemanfaatan Desain dan Digital Marketing untuk Meningkatkan Keterampilan Komersialisasi Produk bagi Siswa SMK Al-Islah - Azmil Chusnaini; Mohamad Yusak Anshori; Reizano Amri Rasyid (Abimanyu : Jornal of Community Engagement, 2026)
In today’s digital economy, the ability to combine creative design with effective marketing strategies has become a key competency in the global creative industry. Vocational education, particularly in design-related fields, plays a crucial role in preparing students to meet these demands. This community service program was conducted at SMK Al-Islah Surabaya, a vocational school specializing in Visual Communication Design (DKV), with the aim of enhancing students’ skills in digital branding and product commercialization. The program involved 40 students and included training and hands-on practice covering branding principles, content creation, social media strategies, and trend analysis. The results showed a significant increase in students’ understanding of branding, from 28% in the pre-test to 85% in the post-test. Students also gained practical experience in producing promotional content and utilizing digital platforms effectively. This program successfully bridged the gap between technical design skills and the application of digital marketing, while also fostering an entrepreneurial mindset among students to better prepare them for the evolving creative industry.